THE IMPORTANCE OF SOLVING SIMPLE AND COMPLEX PROBLEMS IN CHEMISTRY - Махмадражабова, Мужгона (Журнал естественных наук, 2025)
The article presents the experimental pedagogical work the school teachers used when writing papers for the highest qualification category. The educational products of the internship site are not only the expositions created, the lessons conducted, but also the speeches of teachers at scientific and practical conferences of various levels, written abstracts on this topic, seminars for practical teachers.